Societal emotional environments and cross-cultural differences in life satisfaction: A forty-nine country study. Issue 1 (2nd January 2022) - Krys, Kuba; Yeung, June Chun; Capaldi, Colin A.; Lun, Vivian Miu-Chi; Torres, Claudio; van Tilburg, Wijnand A. P.; Bond, Michael Harris; Zelenski, John M.; Haas, Brian W.; Park, Joonha; Maricchiolo, Fridanna; Vauclair, Christin-Melanie; et al.
ABSTRACT: In this paper, we introduce the concept of 'societal emotional environment': the emotional climate of a society (operationalized as the degree to which positive and negative emotions are expressed in a society). Using data collected from 12, 888 participants across 49 countries, we show how societal emotional environments vary across countries and cultural clusters, and we consider the potential importance of these differences for well-being. Multilevel analyses supported a 'double-edged sword' model of negative emotion expression, where expression of negative emotions predicted higher life satisfaction for the expresser but lower life satisfaction for society. In contrast, partial support was found for higher societal life satisfaction in positive societal emotional environments. Our study highlights the potential utility and importance of distinguishing between positive and negative emotion expression, and adopting both individual and societal perspectives in well-being research. Individual pathways to happiness may not necessarily promote the happiness of others.